Fahrenheit 451 [compact disc, unabridged] - Bradbury, Ray, 1920-2012 (Brilliance Audio, 2014)
In Bradbury's futuristic novel, the knowledge gained from books is forbidden, and television replaces deep thought with vapid and menial information. Firefighter Guy Montag is assigned to locate, confiscate, and burn books. He is content with his life and job until he discovers the valuable knowledge found within books. Now, Guy must decide to either continue his stale existence or abscond with his newfound knowledge.